Predicting pediatric tracheal airway size from anthropomorphic measurements. (July 2020) - Fenley, Heather; Voorman, Matthew; Dove, James T.; Greene, Joseph Scott
Abstract: Objectives: To determine the relationship between body mass index and tracheal airway size in children. Methods: Retrospective case series. CT or MRI images of the neck of 171 pediatric patients obtained from 2000 to 2010 at a tertiary pediatric hospital were analyzed. Age, gender, height, weight, BMI and CDC weight classification for each patient were compared with axial CT measurements (AP diameter and width) and calculated cross-sectional airway area. Linear regression models were performed to identify factors predictive of airway size. Results: Age ranged from 2 to 20 years. Weight was the most significant predictor of tracheal AP diameter (P = 0.029), with height also approaching statistical significance (P = 0.051). Tracheal width was best predicted by height (P = 0.09). Weight was the only statistically significant predictor of cross-sectional tracheal area (P = 0.002). Body mass index was not a statistically significant predictor of airway size in any dimension; however, there was an obvious trend towards decreasing tracheal width and cross-sectional area in patients with BMI of 25 or greater. Conclusion: In pediatric patients, estimation of endotracheal or tracheostomy tube size should take into account height, weight and BMI in addition to the patient's age. Patients with elevated BMI may have smaller tracheal sizes in various dimensions than normal or low-weight patients.